2010
DOI: 10.1007/s12350-009-9163-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual gated PET/CT imaging of small targets of the heart: Method description and testing with a dynamic heart phantom

Abstract: The dual gating method improves detection of small moving targets in a phantom and it is feasible in clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
(30 reference statements)
1
26
0
Order By: Relevance
“…This study was conducted without cardiac or respiratory gating as count statistics per gated frame would become insufficient for dynamic quantitative H 2 15 O perfusion imaging. Nonetheless, recent studies have clearly demonstrated that such gating sequences substantially improve spatial resolution 25,26. With the aid of list mode acquisition as well as time-of-flight sequences, future studies will certainly need to focus on the applicability of cardiac and respiratory gating to increase the spatial resolution in dynamic quantitative PET imaging to facilitate measurements of transmural myocardial perfusion gradients 27,28…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted without cardiac or respiratory gating as count statistics per gated frame would become insufficient for dynamic quantitative H 2 15 O perfusion imaging. Nonetheless, recent studies have clearly demonstrated that such gating sequences substantially improve spatial resolution 25,26. With the aid of list mode acquisition as well as time-of-flight sequences, future studies will certainly need to focus on the applicability of cardiac and respiratory gating to increase the spatial resolution in dynamic quantitative PET imaging to facilitate measurements of transmural myocardial perfusion gradients 27,28…”
Section: Discussionmentioning
confidence: 99%
“…Gating simply means dividing the acquired image into individual time-stamped bins that correlate to phases of respiratory and/or cardiac motion by overlaying corresponding time-stamped data [4]. The input signal in the clinical PET/CT image reconstructions based upon gating techniques includes trigger markers indicating the onset of systole and diastole phases on a cardiac signal or inspiration and expiration on a respiration signal.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce motion-related inaccuracies, cardiac and respiratory gating methods are the most common approaches applied in clinical PET imaging [4]. Simultaneous respiratory and cardiac gating, namely dual gating, can reduce motion-related inaccuracies and correspondingly imaging resolution in cardiac PET and oncological applications [5].…”
Section: Introductionmentioning
confidence: 99%
“…Broadly studied techniques to improve temporal resolution and reduce the motion artifacts include cardiac gating utilizing the ECG gating, respiratory gating, and dual gating. These techniques are mainly based on the investigation of electrical state of the heart, the chest wall movement, and the analysis of emission data in clinical studies, respectively [1, 46]. …”
Section: Introductionmentioning
confidence: 99%